Encyclopedia of world's fairs and expositions - Findling, John E.; Lagae, Johan, 1968-; Pelle, Kimberly D. (Jefferson, NC : McFarland & Co., 2008)
"This encyclopedia contains individual histories of each of the nearly 100 World's Fairs and expositions held in more than 20 countries since 1851. Topics covered include goods, tourism, architecture, art and culture"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Exhibitions -- History